PENILAIAN KINERJA KARYAWAN UNTUK KENAIKAN JABATAN DENGAN METODE FUZZY SIMPLE ADDITIVE WEIGHTING (SAW) (Studi Kasus : CV. Asia Exotica) - Tanjung, Dahri Yani Hakim (JURNAL AKADEMIKA, 2016)
This research aims to rank highest based employee performance appraisal to get a promotion campaign using Simple Additive weighting method (SAW) on the CV. Asian Exotica. Great performance appraisal is able to think rationally, not by feeling, if you use the feeling, the valuation becomes ineffective. There are many methods to build a decision support system one of which is by using Simple Additive Wieighting (SAW). This method will provide alternative weighting in accordance with the selection criteria set many. Alternative options with the greatest weight, an alternative option is recommended for selected employees will get promotions objectively, and it is hoped the resulting information can help speed in taking a decision. Employee performance appraisals are conducted by experts using a questionnaire assessment with assessment criteria, namely Cooperation (C1), Discipline (C2), honesty (C3), Initiative (C4), Presence (C5). Perangkingan process undertaken to select an alternative to applying the method of SAW. The results show that the assessment of alternative A5 obtain the highest rank with a value of 1.03. Alternative A5 is an alternative that was selected as the best alternative and the right to sale promotion.